Electronic Bottleneck Suppression in Next‐Generation Networks with Integrated Photonic Digital‐to‐Analog Converters. Issue 2 (3rd February 2021) - Meng, Jiawei; Miscuglio, Mario; George, Jonathan K.; Babakhani, Aydin; Sorger, Volker J.
Abstract : Digital‐To‐Analog Converters In article number 2000033, Volker J. Sorger and co‐workers demonstrate a novel photonic digital‐toanalog converter (DAC) that bypasses the usually deployed optical‐to‐electrical‐to‐optical conversions. Furthermore, this novel parallel binary‐weighted DAC offers high sampling efficiencies and compact form‐factor and is exceptionally suited to be deployed at network‐edges and peripheral sensors. (Image designed by Dr. Mario Miscuglio)